Methionine at the Heart of Anabolism and Signaling: Perspectives From Budding Yeast - Walvekar, Adhish S.; Laxman, Sunil (Frontiers in Microbiology, 2019)
Studies using a fungal model, Saccharomyces cerevisiae, have been instrumental in advancing our understanding of sulfur metabolism in eukaryotes. Sulfur metabolites, particularly methionine and its derivatives, drive and connect various processes integral to metabolism (one-carbon metabolism, nucleotide synthesis, redox balance) with autophagy and epigenetic regulation. The direct involvement of methionine-derived metabolites in diverse chemistries such as transsulfuration and methylation reactions comes from the elegant positioning and safe handling of sulfur through these molecules. In this mini-review, we illustrate cell fate decisions that are governed by methionine, highlighting how this amino acid holds a unique position in both metabolism and cell signaling. We further discuss the interconnections between sulfur and NADPH metabolism, and highlight critical nodes around methionine metabolism that are promising for antifungal drug development.